Hannes Meyer's “Biological ”Concept and its Loosening Influence on Form - Tomita, Hideo (Journal of Asian architecture and building engineering, 2008)
This is a study of forms loosening in German modern architecture. Through computer graphics form analysis, we have explored the design process of Hannes Meyer's (1889-1954) Federal School of the General German Trade Unions Federation (ADGB) (1928-1930). We then verified our conclusions with Meyer's own explanations. In Chapter 2, we have examined the formation of the psychological effects of the glazed corridor during the design process. In Chapter 3, we have clarified the formation of the method known as "dissolution into the landscape" through the analysis of landscape and architecture. Then in Chapter 4, we have explained that a "biological" concept is present in these two methods. Meyer loosened architectural form based on a "biological" concept and presented a new architectural methodology at the end of the 1920s.